Use of Milk Goat Yogurt Lowering Uric Acid, Cholesterol and Blood Glucose - Sujono, S; Bekti, Y; Hikmawan, Ahmad; Saga, A; Yuananda, Y (Universitas Muhammadiyah Surakarta, 2016)
Health is something that has always been observed by any person for the sake of survival. Healthy lifestyle habits should be a society that is able to be applied in daily life - today. Exercise regularly, consumption of nutritious foods and balanced to support a better life. An unhealthy diet , such as eating foods high in fat , salt , sugar -free and low in carbohydrates complex , vegetables and fruits, the main cause of the increased risk of cardiovascular disease , diabetes mellitus and Hyperuricemia ( Sacher , 2004; Kumar et al. 2012). Various types of synthetic drugs used in medicine for example to decrease uric acid , allopurinol denan cause allergic reactions , stomach disorders, bowel , headache , dizziness , fever and blood disorders ( Tjay & Rahardja , 2007). Using of drugs that lower koleserol examples drugs of gemfibrozi drug , fenofibrate and bezafibrat of fibrate acid group which is usually used in patients with type III hiperlipoproteinemia and severe hypertriglyceridemia , has side effects gastrointestinal disturbances such as nausea , diarrhea , flatulence , and others. Class of drugs such as cholestyramine and colestipol resins commonly used in patients with hypercholesterolemia, also give side effects such as nausea, vomiting , and constipation, but is reduced after some time of taking the drug. Likewise, the treatment of chronic hyperglycemia USING insulin and oral antidiabetic drugs are relatively more expensive because of its use in the long term and can cause unwanted side effects. Therefore, it is necessary to find an alternative treatment, especially from natural sources that are safer, does not have efeksamping and effective for use in the treatment of gout, hiperkolesetrolemia and hyperglycemia.